Óleo essencial de limão para controle do bolor verde (Penicillium digitatum sacc.) e bolor azul (Penicillium italicum wehmer) - Mariano, Beatriz Saraiva (Universidade Federal de São Carlos, 2024)
Green and blue molds, caused by the fungi Penicillium digitatum Sacc and Penicillium italicum Wehmer, respectively, have caused damage to citrus fruits, devaluing them for fresh trade. The objective of this study was to evaluate the use of essential oils (EOs), extracted from lemon peel (Citrus limon L. Burmann f.), in the control of these pathogens. EOs extracted from four lemon genotypes were evaluated: Amber, Eureka, Harvey and Siciliano. In experiment 1, the control of P. digitatum by EOs was tested in vitro, using the agar diffusion method. The trial was carried out in a completely randomized design (DIC), in a 4x3 factorial scheme, with four lemon genotypes for EO extraction, three EO concentrations (4, 8 and 16 μL mL-1), with three replications. Plaque evaluations were carried out for seven days. The percentage of inhibition of mycelial growth was calculated for each concentration in relation to the control. In experiment 2, two post-harvest tests were carried out to evaluate the control of the fungi P. digitatum (1) and P. italicum (2) on Tahiti acid lime fruits. The experiments were carried out in DIC, in a 2x4x3 factorial scheme, with two control methods (preventive and curative), four lemon genotypes for EO extraction and three EO concentrations (0, 8 and 16 μL ml-1), with three repetitions per concentration, and ten fruits per repetition. In the preventive treatment, 20 μl of the solution with EO + Tween 80 (1%) was applied to each wound of the fruit and, after 24 hours, 20 μl of a suspension of the pathogen (1x103 conidia/ml for P. digitatum and 1x104 conidia/ml for P. italicum). In the curative control, fungi were inoculated and then solutions with EO + Tween 80 (1%). After pathogen inoculation, measurements of disease lesions were carried out over a period of seven days. The measurements obtained were used to determine the area under the disease progress curve (AACPD). The evaluation data were subjected to analysis of variance and compared using the Tukey test at 5% probability. It was observed in the in vitro test that there was no statistical difference between the genotypes, from day 4 onwards, at concentrations of 8 and 16 μL. In post-harvest trials, with the fungus P. digitatum (1), the Amber genotype showed greater fungal inhibition at a concentration of 16 μL. For the fungus P. italicum (2), at concentrations of 8 and 16 μL, the AACPD was lower in the curative control method compared to the preventive one. It was concluded, in the in vitro test, that EOs at concentrations 8 and 16 μL showed greater inhibition of the growth of Penicillium digitatum. In post-harvest, the Amber genotype, at a concentration of 16 μL, curative method, stood out for its greater fungal inhibition of Penicillium digitatum. Curative treatment showed superiority in inhibiting fungi compared to preventive treatment.
Lemon essential oil to control green mold (Penicillium digitatum sacc.) and blue mold (Penicillium italicum wehmer)
Keywords: Citrus limon; Fungicida; Pós-colheita; Post-harvest; Fungicide; Tahiti acid lime; CIENCIAS AGRARIAS